Centroid model applied for energy scenarios in regions with limited resources - Borges, Toni; Saba, Hugo; Albuquerque, Rosana; Silva, Izete; Nascimento Filho, Aloísio (REVISTA CEREUS, 2022)
The necessity of energy renewal sustained by the use of clean and renewable sources is a worldwide reality, the current efforts that direct these natural resources, increasingly linked to the growth of global energy demand, have a direct impact on the environment. This energy production also has a relevant contribution to the economy and, consequently, to the quality of life of the people present in these production spaces, especially in regions with high levels of social fragility, increasingly present due to the pandemic scenario caused by COVID-19, in this sense, considering the mapping of several economic and social indicators, the study seeks to meet the need to increase energy production in regions with great natural potential but low socio-economic development through a mathematical model based on centroids, identifying optimal location as a parameter for the implementation of renewable power plants in the State of Bahia, aiming to broaden the discussions on the social impacts of these investments and that dialogue with a reality present in several countries around the world.